Мeasurement of d(γ,p) reaction cross sections and asymmetry with linearly polarized coherent bremsstrahlung beam - Brudvik, G.; Burdeinyi, D.D.; Ganenko, V.B.; Hansen, K.; Fissum, K.; Isaksson, L.; Livingston, K.; Lundin, M.; Nilsson, B.; Schröder, B. (Вопросы атомной науки и техники, 2018)
On the base of reaction of deuteron photo-disintegration it was studied possibility of the simultaneous measuring
of cross sections and asymmetry of the (γ,p) reactions at the using of the coherent polarized photon beam. Measurements were performed for the proton emission angle 90°. The cross sections well agree with the literary data, obtained on the bremsstrahlung photon beam in the range of energies 45…80 MeV. На прикладі реакції фотодезинтеграції дейтрона досліджена можливість одночасного вимірювання перетинів і асиметрії (γ,p)-реакції при використанні когерентного поляризованого пучка фотонів. Вимірювання
виконані для кута вильоту протонів 90°. Перетини добре узгоджуються з літературними даними, отриманими на гальмівниму пучку фотонів у діапазоні енергій 45…80 МеВ. На примере реакции фотодезинтеграции дейтрона исследована возможность одновременного измерения
сечений и асимметрии (γ,p)-реакций при использовании когерентного поляризованного пучка фотонов. Измерения проведены для угла вылета протона 90°. Сечения хорошо согласуются с литературными данными,
полученными на тормозном пучке фотонов в диапазоне энергий 45…80 МэВ.